Is Desirable Dietary Pattern (DDP) Related to Stunting in Indonesia? Analysis of Food Consumption Pattern based on DDP Score 2018-2022 (Proceedings of the International Conference on Public Health, 2024)
Indonesia is still struggling with stunting as a public health problem. Food consumption patterns are one of the direct factors that influence nutritional problems. The unbalanced diet of Indonesian people yet, as indicated by the Desirable Dietary Pattern (DDP) score, potentially renders nutritional problems. The study aims to analyze the relationship between DDP score and stunting prevalence during 2018-2022 in Indonesia. This study was a quantitative study with a cross-sectional study design. This study used secondary data DDP scores from the National Food Agency and data on stunting prevalence among children aged 0−59 months from Basic Health Research 2018, Indonesia Child Nutrition Status Survey 2019, stunting prevalence published data 2020 from the Secretariat of the Vice President Indonesia and Indonesia Nutritional Status Survey 2021-2022. The DDP refers to a variety of food and nutrition intake that is calculated based on energy (calorie) consumption, the percentage of different food groups, and numerically stated as a score. The DDP score for a group of foods is calculated by multiplying the energy percentage of each food by a rating, and a higher DDP score indicates a more varied and nutritionally balanced diet. DDP score and stunting prevalence among children aged 0-59 months data were used in this study for five years, from 2018-2022. The results showed that the DDP score 2018-2022 was negatively correlated with stunting prevalence (p
Keywords: desirable dietary pattern, food consumption, stunting, Indonesia